An analysis of life expectancy, economic growth, CO2 emission, health expenditure and urbanization in the D-8 countries - Chan, Huey Shin (2022)
The aim of this research is to investigate the effects of the GDP per capita growth, CO2 emission, health expenditure, and urban population growth on the life expectancy in the D-8 countries. This research utilized panel autoregressive distributed lag model (ARDL) to investigate the relationship between the variables. This research analyses the annual data from 1991 to 2019 for a panel of D-8 countries, Bangladesh, Egypt, Indonesia, Iran, Malaysia, Nigeria, Pakistan, and Turkey. Our empirical findings show that the life expectancy in half of eight countries are affected by health expenditure and urban population growth. We conclude that these two variables influence the life expectancy the most in the D-8 countries. Lastly, this research provides implication for policymakers in outlining the policies in future.